2020
DOI: 10.1111/aab.12646
|View full text |Cite
|
Sign up to set email alerts
|

Combining thermotherapy with meristem culture for improved eradication of onion yellow dwarf virus and shallot latent virus from infected in vitro‐cultured shallot shoots

Abstract: The present study described a combining thermotherapy with meristem culture for improved eradication of onion yellow dwarf virus (OYDV) and shallot latent virus (SLV) from co-infected in vitro-cultured shallot shoots. In vitro-cultured shoots infected with OYDV and SLV were thermo-treated at a constant temperature of 36 C for 0, 2 and 4 weeks, and then meristems (0.5 mm) containing 1-2 leaf primordia were excised and cultured for shoot regrowth. Meristem culture without thermotherapy produced much higher level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 30 publications
3
25
0
Order By: Relevance
“…aggregatum , 10603) was free from Onion yellow dwarf virus (OYDV) and Shallot latent virus (LSV), without thermotherapy, respectively. After heat treatment, 66% and 73% of the 0.5 mm meristematic region became free of those viruses, respectively [ 116 ]. Effectiveness of thermotherapy can be affected by virus type and the host genotype.…”
Section: Virus Elimination By Thermotherapymentioning
confidence: 99%
See 3 more Smart Citations
“…aggregatum , 10603) was free from Onion yellow dwarf virus (OYDV) and Shallot latent virus (LSV), without thermotherapy, respectively. After heat treatment, 66% and 73% of the 0.5 mm meristematic region became free of those viruses, respectively [ 116 ]. Effectiveness of thermotherapy can be affected by virus type and the host genotype.…”
Section: Virus Elimination By Thermotherapymentioning
confidence: 99%
“…Moreover, decreased nucleo/cytoplasma ratio induced by heat treatment was also detected in shallot ( Allium cepa var. aggregatum G. Don, 10603) [ 116 ].…”
Section: Virus Elimination By Thermotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that combining thermotherapy with cryotherapy proved to be the most efficient for elimination of OYDV, LYSV, and garlic common latent virus from garlic (Vieira et al, 2015). However, studies on virus elimination from shallot plants are limited (Putri et al, 2019;Wang et al, 2021).…”
mentioning
confidence: 99%